Length-weight relationship of loose-shell affected Penaeus monodon(Fabricius, 1798) in grow-out system - Mayavu, P; Rajasegar, M; Khan, S Ajmal (Indian Journal of Fisheries, 2011)
Length-weight relationship of loose-shell affected Penaeus monodon(Fabricius, 1798) in grow-out system